Naître et mourir à Nîmes dans l’Antiquité. L’évolution d’un espace funéraire consacré à l’inhumation des nourrissons et des fœtus du Ier siècle avant notre ère au IIIe siècle de notre ère (colline de Montaury, Nîmes, Gard, France) - Gaëlle Granier; Richard Pellé (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
During the Roman period, the burial site on Montaury Hill in Nîmes was located near the western gate of the Augustan enclosure. The rampart, which has been preserved over a length of several hundred metres, was excavated between 2014 and 2019 with a burial space extending from its base. In the burial space, excavated between 2017 and 2019, more than 60 graves were revealed within a small 100 m2 area. These date from the end of the 1st century BC to the beginning of the 3rd century AD. While the burials in the earliest graves, dating to the time of construction of the rampart, are indiscriminate, this area very soon became a specific space for the burial of very young children, from the end of the 1st century AD. The very specific funerary practices are complex and highly variable, showing that great care was given to these burials. They are highly selective: foetuses (sometimes between 5 and 6 months in utero) share the burial space with children who all died before the age of 6 months. The graves of four dogs were found together with the children’s tombs. This preliminary study attempts to understand the societal issues underlying this kind of burial space dedicated to young children, and to gain a better knowledge of the peri-urban landscape of the city through its burial spaces and what they tell us about the organization of Roman society.